INNOVATION ASPECTS OF THE POSTINDUSTRIAL SOCIETY - TOLOCHKO, Svitlana; LYMAR, Valeriia (Trends in education, 2016)
The paper is devoted to innovation aspects of the postindustrial society. It is defined that innovation has been and must continue to be a major driver of rising living standards. Preliminary estimates for several OECD countries show that firms now invest as much in intangible assets related to innovation (R&D, software, skills, organizational know-how and branding) as they invest in traditional capital such as machinery, equipment and buildings. There is growing recognition that innovation encompasses a wide range of activities in addition to R&D, such as organizational changes, training, testing, marketing and design. It is solved following tasks: shown the importance of innovation in postindustrial society; defined the role of knowledge and innovation in postindustrial society; analyzed postindustrial society in the context of innovation development; summarized policy principles of innovation in postindustrial society.
Keywords: innovation; postindustrial society; information-based society; education; knowledge.